2013
DOI: 10.1016/j.celrep.2013.08.017
|View full text |Cite
|
Sign up to set email alerts
|

SLX4 Assembles a Telomere Maintenance Toolkit by Bridging Multiple Endonucleases with Telomeres

Abstract: SummarySLX4 interacts with several endonucleases to resolve structural barriers in DNA metabolism. SLX4 also interacts with telomeric protein TRF2 in human cells. The molecular mechanism of these interactions at telomeres remains unknown. Here, we report the crystal structure of the TRF2-binding motif of SLX4 (SLX4TBM) in complex with the TRFH domain of TRF2 (TRF2TRFH) and map the interactions of SLX4 with endonucleases SLX1, XPF, and MUS81. TRF2 recognizes a unique HxLxP motif on SLX4 via the peptide-binding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
181
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(192 citation statements)
references
References 31 publications
11
181
0
Order By: Relevance
“…It is not known whether mammalian cells deficient for the MUS81 and GEN1 nucleases show loss of telomeric repeats. However, depletion of MUS81 in ALT (alternative lengthening of telomeres) cells, in which telomeres are maintained by HR, results in reduction of specific telomere recombination, telomere loss, and proliferation arrest (Zeng et al, 2009;Wan et al, 2013;Wilson et al, 2013). In contrast, no telomere loss was observed in telomerasepositive cells depleted of MUS81 (Pepe and West, 2014).…”
Section: Discussionmentioning
confidence: 75%
“…It is not known whether mammalian cells deficient for the MUS81 and GEN1 nucleases show loss of telomeric repeats. However, depletion of MUS81 in ALT (alternative lengthening of telomeres) cells, in which telomeres are maintained by HR, results in reduction of specific telomere recombination, telomere loss, and proliferation arrest (Zeng et al, 2009;Wan et al, 2013;Wilson et al, 2013). In contrast, no telomere loss was observed in telomerasepositive cells depleted of MUS81 (Pepe and West, 2014).…”
Section: Discussionmentioning
confidence: 75%
“…[30][31][32] It has been also reported that As 2 O 3 treatment leads to damage to telomeres. 33 We then studied whether Mus81 sumoylation was involved in DNA damage responses after exposure to metal toxins including arsenic and chromium .…”
Section: Compromised Dna Damage Response In Cells Expressing Mus81-5rmentioning
confidence: 99%
“…Slx4 and Saw1 are proposed to function as scaffolds that assemble XPF and other structure-specific endonucleases (Lyndaker and Alani 2009;Kashiyama et al 2013;Li et al 2013;Wan et al 2013). In contrast to budding yeast (Flott et al 2007;Li et al 2008), neither slx4Δ nor saw1Δ is sensitive to UV or MMS in fission yeast (Figure S3 and (Coulon et al 2006).…”
Section: Rad16-249 Has Genetic Interactions With Other Dna Damage Repmentioning
confidence: 99%
“…Finally, we observed sensitivity to hydroxyurea (HU) in rad16-249 and rhp14Δ mutants, but again not in rad13Δ. HU causes fork stalling due to nucleotide depletion, and restart occurs via recombination-based mechanisms (Meister et al 2007;Lambert et al 2010;Sabatinos et al 2012).Slx4 and Saw1 are proposed to function as scaffolds that assemble XPF and other structure-specific endonucleases (Lyndaker and Alani 2009;Kashiyama et al 2013;Li et al 2013;Wan et al 2013). In contrast to budding yeast (Flott et al 2007;Li et al 2008), neither slx4Δ nor saw1Δ is sensitive to UV or MMS in fission yeast (Figure S3 and (Coulon et al 2006).…”
mentioning
confidence: 99%